Homocysteine is a bystander for ST-segment elevation myocardial infarction: a case-control study - Chen, Ching-Yu Julius; Yang, Tzu-Ching; Chang, Christopher; Lu, Shao-Chun; Chang, Po-Yuan (BMC cardiovascular disorders, 2018)
Homocysteine has been long considered a risk factor for atherosclerosis. However, cardiovascular events cannot be reduced through homocysteine lowering by B vitamin supplements. Although several association studies have reported an elevation of serum homocysteine levels in cardiovascular diseases, the relationship of homocysteine with ST-segment elevation myocardial infarction (STEMI) is not well established. We prospectively enrolled STEMI patients who were consecutively admitted to an intensive care unit following coronary intervention in a single medical center in Taiwan. Control subjects were individuals who presented to the outpatient or emergency department with acute chest pain but subsequently revealed patent coronary arteries by coronary arteriography. The association between serum homocysteine levels and STEMI was investigated. A culture system using human coronary artery endothelial cells was also established to examine the toxic effects of homocysteine at the cellular level. Patients with chest pain were divided into two groups. The STEMI group included 56 patients who underwent a primary percutaneous coronary intervention. The control group included 17 subjects with patent coronary arteries. There was no difference in serum homocysteine levels (8.4 ± 2.2 vs. 7.6 ± 1.9 μmol/L, p = 0.142). When stratifying STEMI patients by the Killip classification into higher (Killip III-IV) and lower (Killip I-II) grades, CRP (3.3 ± 4.1 vs. 1.4 ± 2.3 mg/L, p = 0.032), peak creatine kinase (3796 ± 2163 vs. 2305 ± 1822 IU/L, p = 0.023), and SYNTAX scores (20.4 ± 11.1 vs. 14.8 ± 7.6, p = 0.033) were significantly higher in the higher grades, while serum homocysteine levels were similar. Homocysteine was not correlated with WBCs, CRP, or the SYNTAX score in STEMI patients. In a culture system, homocysteine at even a supraphysiological level of 100 μmol/L did not reduce the cell viability of human coronary artery endothelial cells. Homocysteine was not elevated in STEMI patients regardless of Killip severity, suggesting that homocysteine is a bystander instead of a causative factor of STEMI. Our study therefore supports the current notion that homocysteine-lowering strategies are not essential in preventing cardiovascular disease.